TEACHING WRITING NARRATIVE PARAGRAPH THROUGH STIMULI QUESTION TECHNIQUE TO THE TENTH GRADE STUDENTS OF STATE HIGH SCHOOL 1 OF PALEMBANG - Magdad Hatim; Noviati Noviati; Heni Kurnia (ELTE Journal (English Languange Teaching and Education), 2020)
The main problem of this research was “Is it effective to teach writing narrative through stimuli questions technique to the tenth-grade students of State High School 1 of Palembang?”. Therefore, the main objective of this research was to find out whether or not it was effective teaching writing narrative paragraphs through the stimuli question technique to the tenth-grade students of State High School 1 of Palembang. The method of this research was the experimental method. The population of this study was the tenth-grade students of State High School 1 of Palembang, in the academic year of 2016/2017. The sample of this study was 39 students who were chosen by convenience sampling. The data were collected through two kinds of tests, pre-test, and post-test. The data were analyzed by a matched t-test. Based on the results of the data analysis, it was found that the students’ average score in the pre-test was 59.1, and the students’ average score in the post-test was 68.6. Based on the matched t-test calculation, it was found out that the t-obtained was 8.84. the critical value of a 5% significance level was 1.684. it showed that t-obtained was higher than the t-table. From this study, it was found that teaching writing narrative paragraphs through stimuli questions technique to the tenth-grade students of State High School 1 of Palembang was effective.